(untitled) (Journal of Universal Science Research, 2025)
Child and adolescent mortality is one of the common problems affecting virtually all countries worldwide. The ongoing efforts to reduce child and adolescent mortality rates annually, the diversity of causes, types, and forms of fatal incidents, as well as the necessity to determine the prevalence of such cases in the Republic of Uzbekistan, have further heightened interest in studying this issue.